Analysis of Connotation Words in The Jakarta Post Online Headline News - Eva Nurul Candra; Elyza Martiarini (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
This research aims to analyse connotation words in the Jakarta Post online headline news and to find the positive and negative connotation of those online headline news. Qualitative method and descriptive analysis are applied in this research. There are 30 headline news of data sources. The result of the research shows that 46,66 % of the 30 headline news online use positive connotation words and 53,33 % of them use negative connotation words in the news. And it also shows that an online newspaper headline might evoke different feelings and emotions to the readers by using the connotation words. This finding implies that the most connotation words used in the headline news is negative connotation. Key words : connotation words, the Jakarta Post online headline news